Perancangan Game Edukasi berbasis Android pada Mata Pelajaran Bahasa Inggris Kelas X di SMAS Pertiwi 2 Padang Tahun Ajaran 2025/2026 - Pratama, Riki Denata; Wijaya, Indra; Yunus, Yuliawati (LPPM Institut Pendidikan Nusantara Global, 2025)
Android-based educational games bring a new way to make English learning more engaging for tenth-grade students at SMA Swasta Pertiwi 2 Padang in the 2025/2026 academic year. The aim is to test the validity, practicality, and effectiveness of the developed game so it can be applied as a classroom medium. This study used a Research and Development (R&D) approach with the 4D model: Define, Design, Development, and Disseminate. Thirty students took part as participants, and data were collected through questionnaires from validators and learners, then analyzed with Microsoft Excel. Findings reveal that the game reached an average validity score of 87.41%, categorized as highly valid. Practicality scored 85.71%, showing the game is user-friendly and appropriate for students. Effectiveness reached 89.53%, proving the game improves learning activities and strengthens engagement. These results demonstrate that the application not only meets academic and technical standards but also supports an enjoyable and motivating learning process. In conclusion, the Android-based educational game is valid, practical, and effective, making it a promising tool to support English language learning in high school.